Entrepreneurial Intentions of Accounting and Management Students - Agustina, Tri Siwi; Fitdiarini, Noorlaily; Heru, Aria (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to examine the effects of entrepreneurial attitudes towards entrepreneurial intentions with entrepreneurship course as a mediating factor. This study used a survey method with 382 respondents that included Accounting and Management Science students from the Faculty of Economics and Business, Airlangga University who took an Entrepreneurship course in even semester. The data in this study were analyzed using Partial Least Square (PLS) with PLS version 3.0 software. The results showed that entrepreneurial attitudes affected entrepreneurial intentions and entrepreneurship course. Entrepreneurship course also partially mediated the effect of entrepreneurial attitudes on the entrepreneurial intentions of accounting and management students.